PENGARUH MODEL PEMBELAJARAN TEAM GAME TOURNAMENT TERHADAP MOTIVASI BELAJAR GEOGRAFI SISWA KELAS X SMAN 10 MALANG - Bayu Adi Nugraha; - - Sumarmi; - - Purwanto (Media Komunikasi Geografi, 2016)
Applied learning model that teachers in schools can affect motivation for geography students. Students are reluctant to geography lesson for the learning tends to be boring and lacking implementation. This study aims to determine the effect of learning model Team Game Tournament against students' motivation to learn geography. This study is a quasi-experimental research with pretest-posttest control group design. Collecting data using questionnaires. The results showed that there are significant learning model Team Game Touranment on motivation to learn geography student, it is proved by testing the hypothesis by using t-test with a result of 0,000 <0,05 and gain score greater experimental class is 6.83, while the control class 2.69. Keywords: Learning model, Team Game Tournament, motivation to learn geography.